ETIKA BERBAGINASI: ANALISIS ETIKA BERBAGI PADA ORANG YANG MEMBUTUHKAN DALAM ASPEK KEMANUSIAAN, MEMAHAMI RASA BERSYUKUR - Danang Nugroho; Andito Nugroho; Iwa Wijayanto; M Rifki Maulana Fauzi; Maulana Nugraha; Mochamad Latief; Muhamad Ihsan Ansori; Wahyudin (JURNAL ILMIAH RESEARCH STUDENT, 2024)
This article explores ethical concepts in exploring humanity and the meaning of gratitude with a focus on the practice of sharing rice. Sharing is a social phenomenon in which individuals or groups contribute voluntarily to share resources with others in society. Ethics and sharing are terms that refer to moral principles and behavior that encourage individuals to pay attention to the needs of others. In this case, sharing rice can be a symbol of love and blessings that can strengthen relationships between individuals and increase feelings of loyalty and solidarity in society. This research aims to investigate how ethics plays a key role in the success and positive impact of rice sharing as well as improving the quality of social relationships, especially in the context of rice sharing. The main aim of this research is to understand the link between ethics, sharing, and the role of gratitude in creating a more empathetic and sustainable society.